MRI Evaluation of Degenerative Lumbar Spine in Population Of Eastern Nepal - Ranabhat, Nawaraj; Bhattarai, Rakshya; Basnet, Prasansa; Banjade, Udaya Raj; Pande, Shreebridhi; Sapkota, Suhail; Sherpa, Diki (Nepalese Journal of Radiology, 2023)
Introduction: Low back pain is the most commonly encountered symptom, with approximately 80% of individuals experiencing at least one instance of back pain throughout their lifetime. Magnetic resonance imaging is widely regarded as a highly effective diagnostic tool for assessing different factors contributing to back pain. Methods: The study included all patients who had a history of chronic low back pain and were referred for Magnetic resonance imaging at the Radiology Department of Nobel Medical College between September 1, 2020, and September 1, 2021. These patients were suspected to have degenerative diseases of the lumbar spine. Results: A total of 120 patients were included in the study, with ages ranging from 28 to 81 years (mean: 53.38 ± 11.5 years). Among these patients, 64 individuals (53.3%) were females. The most common finding observed was disc desiccation, which was present in 115 patients (95.8%). The prevalence of degenerative findings increased with age, indicating a correlation between age and degenerative changes in the lumbar spine. Conclusions: The study’s conclusion states that Magnetic resonance imaging is the most sensitive imaging technique for evaluating low back pain related to degenerative changes. The use of Magnetic resonance imaging is recommended due to its lack of known side effects, absence of radiation exposure, and noninvasive nature. It was found that various types of degenerative changes can be present in symptomatic patients aged over 40.